2014
DOI: 10.1007/s40314-014-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of the errors of the averaged models in the restricted three-body problem in a short time scale

Abstract: The objective of the present research is to study the accuracy of the double-and single-averaged models that are usually considered to predict the motion of spacecrafts or celestial bodies that have their motion perturbed by a third-body. Those two models are compared with each other and then validated against the complete elliptic restricted threebody problem. Those models are developed to give a faster but general behaviour of the motion of the perturbed body in a medium or longer time scale. The researches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The equations of motion used in the present research were studied in details in Domingos et al (2014). The present paper summarizes the final results, in the form used here to perform the numerical integrations that evaluate the lifetime of the spacecraft.…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The equations of motion used in the present research were studied in details in Domingos et al (2014). The present paper summarizes the final results, in the form used here to perform the numerical integrations that evaluate the lifetime of the spacecraft.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Different initial eccentricities (0.0, 0.05, 0.10, 0.15 and 0.20) are considered for the orbit of the moon, which means that, in a system fixed in the moon, those are the eccentricities of the disturbing body, the planet. Those choices are made based on Domingos et al (2013Domingos et al ( , 2014, which showed that averaged models have good accuracy up to those values. The system used as an example for the present studies has the same physical data (masses and distances) of the Earth-Moon system, but considers possible eccentricities for the orbit of the secondary body around the primary.…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, ref. [18] used the solution obtained by [19] for the three-body elliptical problem and obtained the lifetime for the Earth-Moon system as a function of the initial eccentricities and inclinations of the probe. In [20], lifetime maps were obtained for the Callisto-Jupiter system assuming different values for the eccentricity of the perturbing body, also taking into account the J 2 and the order 2 of the sectoral flattening coefficient, C 22 , of Callisto.…”
Section: Introductionmentioning
confidence: 99%